2011
DOI: 10.1016/j.jbiotec.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant antigen production for assays of intradermoreaction for diagnosis and surveillance of tuberculosis

Abstract: The goal of the present work was to develop reagents with potential for tuberculosis diagnosis. Genetic sequences of Mycobacterium tuberculosis secretion antigens were amplified by PCR, cloned into the Gateway(®) system, and expressed in Escherichia coli. The recombinant M. tuberculosis proteins were purified by metal affinity chromatography and preparative gel SDS-PAGE electrophoresis followed by electroelution and removal of endotoxins using Triton X-114. In total, seven recombinant proteins were obtained (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Lymphocyte proliferation assays and dermal reactivity were used to characterize and compare the delayedtype hypersensitivity reactions induced, and guinea pigs have continued to be useful for evaluating reagents which are used for diagnostic skin tests (Haslov et al 1984(Haslov et al , 1995Malaghini et al 2011). However, compared with other laboratory animal species, there has been limited development of immunological reagents specific for the guinea pig.…”
Section: Immune Responsementioning
confidence: 99%
“…Lymphocyte proliferation assays and dermal reactivity were used to characterize and compare the delayedtype hypersensitivity reactions induced, and guinea pigs have continued to be useful for evaluating reagents which are used for diagnostic skin tests (Haslov et al 1984(Haslov et al , 1995Malaghini et al 2011). However, compared with other laboratory animal species, there has been limited development of immunological reagents specific for the guinea pig.…”
Section: Immune Responsementioning
confidence: 99%
“…The animal model chosen for this study was C. porcellus, because it is a well-established animal model to study DTH in different types of diseases and is also used in the investigation of several infectious diseases [16][17][18][19][20] . Furthermore, some studies on the genetics of guinea pig have shown immunological analogies between these species 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, guinea pigs are better animal models to be used in an industrial qualitative control process. Moreover, they are already used as bio models for skin test antigen evaluation in tuberculosis 19 , leprosy 22 , and immunodeficiency virus type 1 infection 20 . Additionally, the process of experimental infection in hamsters is time consuming and requires well-trained professionals 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these antigens, early secretory antigenic target 6 (ESAT-6; ESXA, Rv3875), ESAT-6-like protein esxB (CFP10; ESXB, Rv3874), Pro-Pro-Glu 68 (PPE68; Rv3873) and Pro-Glu 35 (PE35; Rv3872) are immunodominant (3)(4)(5). The former two antigens (ESAT-6 and CFP10) have been investigated in detail in humans and are known to be predominant virulence factors (6,7) and in addition are good candidates for the diagnosis of tuberculosis (TB) (8). The latter two, PE35 and PPE68, are members of the PE/PPE family and exhibit immunodominance (9).…”
Section: Introductionmentioning
confidence: 99%